Profile of Students' Critical Thinking Skills in 3D Module Learning Material on Gas Kinetic Theory with Inquiry Model - Lintangesukmanjaya, Rahmatta Thoriq; Prahani*, Binar Kurnia; Marianus, Marianus; Wibowo, Firmanul Catur; Costu, Bayram; Arymbekov, Beken (Jurnal Pendidikan Sains Indonesia, 2024)
The increasingly difficult educational challenges and needs in today's modern world require interactive learning. The research was conducted to know students' critical thinking skills (CTS) in the kinetic gas theory material. Another goal is, as an initial observation, to develop learning methods with guided inquiry learning models assisted by android-based 3D modules in kinetic gas theory material. The research population was all class XI students at Tuban 2 Public High School in 2022/2023 as majoring in Mathematics and Natural Sciences. The research was conducted in 5 classes with the same distribution of questions and questionnaires. As secondary data, the researcher added several articles relevant to the research. The results of this study using several questions on kinetic gas theory material for class X1 were that students needed to be more able to answer each question with indicators of critical thinking. The student's obstacle in answering the questions lies in the need for more understanding of kinetic gas theory material and the not yet maximal use of the method in the current teaching and learning process. The resulting inquiry learning in the future will change the CTS of Tuban 2 Public High School students in the kinetic gas theory.